Development of an LPPBJ Accreditation System as an Implementation of Digital Governance in Public Procurement - Sutresna Wati; Rizky Dwi Raharjo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study addresses the challenge of translating regulatory accreditation requirements into executable and secure information system workflows for public procurement training providers (LPPBJ). Current accreditation practices often rely on manual procedures and fragmented digital tools, resulting in limited traceability and increased information security risks. To address these issues, an LPPBJ accreditation system is developed using a business process–driven system development approach in accordance with the Decree of the Head of the National Public Procurement Agency (LKPP) Number 201 of 2024. Regulatory provisions are analyzed and modeled using Business Process Model and Notation (BPMN) and subsequently implemented into an integrated information system that enforces workflow constraints across accreditation submission, document management, assessment, scoring, and result determination. The system integrates the assessment process directly within the application, enabling controlled, system-based evaluation by assessors. Role-based access control and audit trail mechanisms are applied to enhance document security, confidentiality, and process traceability. The results show that the proposed system improves regulatory compliance, process integration, and accountability, demonstrating the effectiveness of BPMN-based development for compliance-oriented digital governance systems.